Incorporating storytelling into the medical curriculum - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava; Harshal Mendhe; Abhishek Joshi (Wolters Kluwer Medknow Publications, 2023)
Effective delivery of medical education depends on a number of factors and the role of every stakeholder is crucial to ensure the development of competent medical graduates. Storytelling in the delivery of medical education essentially refers to the employment of narratives, anecdotes, and real-life experiences to stories to share and teach medical concepts and principles. Storytelling offers a wide range of benefits to medical students and empowers them to become better and more compassionate clinicians. Each medical institution must explore the possibility of introducing storytelling within the medical curriculum to benefit students in terms of the attainment of their learning outcomes. In conclusion, storytelling in medical education is a teaching-learning method that can play its part in the development of empathy, promoting cultural understanding, and creating ethical awareness. Considering the merits of storytelling, it is the need of the hour to adopt a systematic plan to enable its integration and move forward in a journey toward creating more empathetic and culturally competent medical doctors.